Endocrine biomarker responses during an intercollegiate wrestling season - Ransone, J. W.; Finn, K. J. (International Journal of Wrestling Science, 2020)
The aim of the current investigation was to quantify the endocrine biochemical markers including testosterone (T), cortisol (C), secretory immunoglobin A (sIgA) and testosterone: cortisol ratio (T:C) as indicators of the balance between anabolic and catabolic processes quantifying the homeostatic response to late competitive phase of the college wrestling season using a longitudinal repeated measures design. A volunteer sample of ten collegiate wrestlers (age = 22.11 ± 1.1yrs, height = 177.8 ± 3.1cm; weight = 77.6 ± 20.9kg) gave saliva samples via unstimulated passive drool (@0.75 mL) at 24 hours before and 24-48 hours post competition. All biomarker concentrations were determined using indirect enzyme-linked immunosorbent assay (ELISA) kits. Time since awake for each sample, whether the team traveled, number of competitions, day of the study, and trial (pre vs. post) was recorded to test for effect and interactions on biomarker concentrations. Conceptualizing the change in T, C, T:C ratio and sIgA over the competitive season, a series of hierarchical linear models were utilized. Our analyses revealed that cortisol and testosterone concentrations were predicted by day of study, time since awake, and number of competitions; however, T:C ratio was only predicted by day of the study and trial, indicating that as the season progressed, T:C ratio decreased over time after competitions. Secretory IgA was predicted by number of competitions indicating a decrease in sIgA as bouts increased, sIgA decreased. The exploration of salivary biomarkers could be conceptualized as an objective method to understand demands of competitive exposures on several physiological systems.